1984
DOI: 10.1144/gsl.sp.1984.017.01.47
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosed ophiolitic rocks from the Serbo-Macedonian Massif, near Lake Volvi, North-east Greece

Abstract: The paper describes preliminary results from the 120sqkm Volvi mafic complex within the Greek Serbo-Macedonian Massif. We conclude from published information and isotopic ages that the central and eastern part of the Massif (basement and Triassic/Jurassic cover) were affected by an amphibolite-facies regional metamorphic and deformational event in the Late Jurassic-Early Cretaceous. Delayed uplift from this same event may explain Tertiary ages from Kerdilion migmatites. The Volvi complex may thus be A: pre-Mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
18

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 11 publications
0
56
0
18
Order By: Relevance
“…1a) corresponds to the upper part of the Serbo-Macedonian Massif. It consists of a pile of thrust units affected by HP metamorphism (Dixon and Dimitriadis 1984;Michard et al 1994) that were emplaced toward the WSW likely in Cretaceous times (Burg et al 1990(Burg et al , 1996. To the north of the SRCC, the Sideroneron Gneiss Unit (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…1a) corresponds to the upper part of the Serbo-Macedonian Massif. It consists of a pile of thrust units affected by HP metamorphism (Dixon and Dimitriadis 1984;Michard et al 1994) that were emplaced toward the WSW likely in Cretaceous times (Burg et al 1990(Burg et al , 1996. To the north of the SRCC, the Sideroneron Gneiss Unit (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Turpaud and Reischmann [2010] showed that in the Figure 2. Tectonic map of the Rhodope Metamorphic Province modified after Burg et al [1996], Ricou et al [1998], Bonev et al [2006], and Dixon and Dimitriadis [1984]. Rectangle indicates the study area (Figure 4).…”
Section: Rhodope Terrane: Sidironero Unit and Related Unitsmentioning
confidence: 99%
“…Kostopoulos et al [2000] found evidence for the former presence of diamond, and hence UHP metamorphism, in rocks of the Vertiskos Unit and the CircumRhodope Belt (see section 2.6). Metamorphic mafic and ultramafic rocks, the Volvi Ophiolites, occur in the basal part of the Vertiskos Unit, close to its boundary against the Kerdilion unit [Dixon and Dimitriadis, 1984].…”
Section: Strandja Autochthonmentioning
confidence: 99%
“…The rocks of the Vertiskos Terrane underwent amphibolite-facies metamorphism and a retrograde greenschist-facies overprint (e.g. Dixon and Dimitriadis 1984;Kilias et al 1999). Because all contacts are tectonic, there is no clear relationship with the surrounding country rocks.…”
Section: Geological Settingmentioning
confidence: 99%
“…The mafic-ultramafic rocks have generally been assigned to the so-called Therma-Volvi-Gomati (TVG) Complex (e.g. Dixon and Dimitriadis 1984) and commonly been interpreted as either a remnant of the Palaeotethys Ocean that closed in the Early Jurassic (Ş engör et al 1984) or, in contradiction, as a rift-related intrusive complex of Mesozoic age (Dixon and Dimitriadis 1984). In comparison, Brun and Sokoutis (2007) suggest that the boundary between the Kerdillion Unit and the Vertiskos Terrane is represented by the WSW-dipping Kerdillion detachment (Fig.…”
Section: Geological Settingmentioning
confidence: 99%